Community Initiation of The Kaba Indah Lestari Group In Forest Management - Tia Yuanta; Heni Nopianti; Diyas Widiyarti (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
This research aims to see what contributions are obtained and given by the kaba indah lestari women's group both for their own group, the community and the forest area. This research used a qualitative approach, described descriptively. Data collection was done by non-participant observation, unstructured interviews. Data analysis using Miles and Huberman data analysis techniques includes data collection, data reduction and data presentation. The theory used in analyzing the results of this research is Social Feminist theory. This research found several findings, namely the Kaba Indah Lestari Women Farmers Group gained access to manage the forest through a social forestry scheme with a conservation partnership, so that they could manage the land with several provisions. The activities carried out by the Kaba Indah Lestari Women Farmers Group are not only gardening, they also innovate by making processed food from their garden products such as coffee sticks, bags from plastic sachet drink packaging and bags from handicrafts. The Kaba Indah Lestari Women Farmers Group has made a good contribution in land management by growing vegetables organically so as to minimize soil and environmental pollution while caring for trees that have been planted by the forestry. The Kaba Indah Lestari Women Farmers Group has been independent and has an impact on the surrounding community through the program of sharing basic food and vegetables for the elderly and children who are prone to stunting.Keywords: Forest, Women Farmers Group, Contribution,s Management